Monitoring of quality control on two Automated Hematology Analyzer Sysmex XN-1000 (L) and XN-1000 (R) / Siti Farhah Mohd Hanim - Mohd Hanim, Siti Farhah (2014)
The aim of the present study was to monitor and evaluate the Quality Control daily results of Automated Hematology Analyzer Sysmex XN-1000 (L) and XN-1000 (R). In this study, quality control materials were used to conduct the analytical procedure. The result obtained from QC procedure was analyzed based on the Levey-Jennings chart to evaluate whether the procedure was in-control or out-of- control. Based on the QC data, the mean and stardard deviation were calculated to plot the Levey-Jennings chart. The values of the Coefficient of Variation obtained from the both of analyzers were compared to determine the more precise analyzer. The parameter included in this study is Red Blood Cell (RBC), Hemoglobin (HB), Hematocrit (HCT), Platelet (PLT) and White Blood Cell (WBC). The method used in this study may help to identify quality problem that can be connected while data are being collected, and to identify biases in data collection that might be adjusted later. Further studies are required for proper quality control and calibration to optimizing the reliability of the patient results.